Family socio-economic status, mother’s psychosocial skills and children’s human capital: evidence from four low- and middle-income countries - Georgiadis, A; Hermida, P (Palgrave Macmillan, 2014)
Family background has been considered one of most important factors associated with child development across different settings (Brooks-Gunn and Duncan 1997; Grantham-McGregor et al. 2007). Evidence from industrialized countries supports a strong link between different background factors, such as parental socio-economic status (SES), and parental cognitive and psychosocial skills on the one hand, and children’s cognitive and psychosocial skills on the other; these factors in turn are important determinants of educational achievement, earnings, and other key outcomes in later life (Osborne-Groves 2005a; Cunha et al. 2006; Blanden et al. 2007).